Metal organic framework membranes for carbon dioxide separation. (3rd March 2015) - Venna, Surendar R.; Carreon, Moises A.
Abstract: In this paper we review research progress on metal organic framework membranes which have demonstrated ability to separate carbon dioxide from different light gases. More specifically, we focus mainly on CO2 /N2, CO2 /CH4, and CO2 /H2, gas separations which are highly relevant compositions in flue gas treatment, natural gas purification, and hydrogen purification, respectively. We also discuss several conventional and novel strategies developed by several research groups for the continuous defect-free MOF membrane fabrication. Finally, the advantages of using MOFs in mixed matrix membranes and improvements in gas separation performances with the MOF based mixed matrix membranes are presented. Graphical abstract: Highlights: Progress on metal organic framework membranes for CO2 separation is reviewed. The paper focuses mainly on CO2 /N2, CO2 /CH4, and CO2 /H2 gas separations. Strategies for the continuous defect-free MOF membrane fabrication are discussed. Advantages of using MOFs in mixed matrix membranes are presented.